Ifo survey data in business cycle and monetary policy analysis - Sturm, Jan-Egbert; Wollmershaeuser, Timo. (Heidelberg ; New York : Physica-Verlag, 2005)
The present volume, based on a conference entitled "The Academic Use of Ifo Survey Data", gives examples of timely research questions which can be addressed by qualitative survey data like the monthly Ifo Business Survey. It shows that this type of real-time data can be very informative when it comes to forecasting real economic activity or exploring monetary policy transmission.
Includes bibliographical references.
oif 27/07/16
Loans
Keywords: Business forecasting; Monetary policy